The Semaphorin 3A Inhibitor SM-345431 Accelerates Peripheral Nerve Regeneration and Sensitivity in a Murine Corneal Transplantation Model - Omoto, Masahiro; Yoshida, Satoru; Miyashita, Hideyuki; Kawakita, Tetsuya; Yoshida, Kenji; Kishino, Akiyoshi; Kimura, Toru; Shibata, Shinsuke; Tsubota, Kazuo; Okano, Hideyuki; Shimmura, Shigeto (PLOS ONE, 2012)
Background Peripheral nerve damage of the cornea is a complication following surgery or infection which may lead to decreased visual function. We examined the efficacy of the semaphorin 3A inhibitor, SM-345431, in promoting regeneration of peripheral nerves in a mouse corneal transplantation model. Methodology/Principal Findings P0-Cre/Floxed-EGFP mice which express EGFP in peripheral nerves cells were used as recipients of corneal transplantation with syngeneic wild-type mouse cornea donors. SM-345431 was administered subconjunctivally every 2 days while control mice received vehicle only. Mice were followed for 3 weeks and the length of regenerating nerves was measured by EGFP fluorescence and immunohistochemistry against βIII tubulin. Cornea sensitivity was also measured by the Cochet-Bonnet esthesiometer. CD31 staining was used to determine corneal neovascularization as a possible side effect of SM-345431. Regeneration of βIII tubulin positive peripheral nerves was significantly higher in SM-345431 treated mice compared to control. Furthermore, corneal sensitivity significantly improved in the SM-345431 group by 3 weeks after transplantation. Neovascularization was limited to the peripheral cornea with no difference between SM-345431 group and control. Conclusions/Significance Subconjunctival injections of SM-345431 promoted a robust network of regenerating nerves as well as functional recovery of corneal sensation in a mouse keratoplasty model, suggesting a novel therapeutic strategy for treating neurotrophic corneal disease.